Reflection measurement and visual evaluation of the luminosity of skin coated with powder foundation. Issue 1 (31st May 2012) - Ikeda, Naoko; Miyashita, Kyoko; Hikima, Rie; Tominaga, Shoji
<x xml:space="preserve">Abstract</x> This article aims to identify the essential components of the luminosity of skin coated with powder foundation, based on two processes: reflection measurement and visual evaluation of the skin surface. The luminosity refers to the state of being "luminous, " "brilliant, " or "radiant" of the foundation‐coated skin. First, a flat piece of artificial skin is used, and an experimental device is developed to visually evaluate the appearance of the foundation‐coated artificial skin at different conditions of viewing angle, illumination angle, and illumination intensity. The luminosity score is analyzed from the point of view of optical reflection. Next, the same assessment of luminosity is executed for real human skin. The luminosity is evaluated for cheek and forehead coated with powder foundation at different observation conditions using another experimental device. Finally, all luminosity scores are analyzed in color spaces to identify the color region relating to luminosity perception. © 2012 Wiley Periodicals, Inc. Col Res Appl, 39, 45–55, 2014